1877-1878 Osmanlı - Rus Harbi Belgeleri: Abdi Paşa'nın Muhakemesi - Öztürk, Mustafa (Türk Tarih Kurumu [EN], 2002)
Konuya adını verdiğimiz belgeler, 1877-1878 Osmanlı-Rus Savaşı sonunda Rumeli'deki başarısızlığı dolayısıyla Divan-ı Harbe verilen Abdi Paşa'nın mahkemesine ait belgelerdir. Belgelerin incelenmesinden de anlaşılacağı gibi, bu belgeler, mahkemenin bütün seyrini şâmil olmayıp, savcı Ali Nizami Paşa'nın iddianamesi ve buna karşılık Abdi Paşa'nın savunmasını ihtiva eden belgelerdir.

The documents giving the title to this study pertain to the trial of Abdi Pasha, who was brought before the Divan-ı Harb due to his failure in Rumelia at the conclusion of the 1877–1878 Ottoman–Russian War. As can be understood from the examination of the documents, they do not encompass the entirety of the proceedings of the court; rather, they consist of the indictment prepared by the prosecutor Ali Nizami Pasha and Abdi Pasha’s corresponding defense.
Documents of the 1877–1878 Ottoman–Russian War: The Trial of Abdi Pasha
Keywords: General Turkish History (Other); Genel Türk Tarihi (Diğer)